2013
DOI: 10.1161/jaha.112.000091
|View full text |Cite
|
Sign up to set email alerts
|

Beta and Angiotensin Blockades Are Associated With Improved 10‐Year Survival in Renal Transplant Recipients

Abstract: BackgroundMortality in allograft kidney transplant recipients is high, and cardiovascular disease is the leading cause of death in these patients. They have heightened activity of sympathetic and renin–angiotensin systems. We tested the hypothesis that blockade of sympathetic and renin–angiotensin systems in these patients may offer a survival benefit using a large cohort of patients with long‐term follow up.Methods and ResultsMedical records of 321 consecutive patients from our institution who had received re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(11 citation statements)
references
References 46 publications
0
11
0
Order By: Relevance
“…RTRs usually have heightened activity of the sympathetic nervous system so therapy with BB may offer a survival benefit. Some observational reports showed that therapy with BB is associated with better long-term survival of RTRs [9]. These facts may have influenced the wide use of BB among our cohort of RTRs.…”
Section: Discussionmentioning
confidence: 89%
“…RTRs usually have heightened activity of the sympathetic nervous system so therapy with BB may offer a survival benefit. Some observational reports showed that therapy with BB is associated with better long-term survival of RTRs [9]. These facts may have influenced the wide use of BB among our cohort of RTRs.…”
Section: Discussionmentioning
confidence: 89%
“…However, data from the United States Renal Data System indicate that only 20% of the chronic dialysis patients with heart failure were receiving beta-blocker therapy [11,13]. In a 10-year study of renal transplant patients, beta-blocker therapy was associated with improved survival (HR 0.61, p = 0.04) compared with not being on a beta-blocker, and this was consistent, regardless of the presence of HTN, diabetes, myocardial infarction or left ventricular dysfunction [14]. …”
Section: Discussionmentioning
confidence: 99%
“…Of these, we excluded 12 for the following reasons: 6 provided insufficient data; 4 study pairs investigated the same population, so we excluded the 4 with the shortest follow‐up, smallest population, or least complete outcome; 1 study was only reporting a protocol and 1 study used ACEI/ARBs in both the experimental and control arms. Therefore, 24 studies involving a total of 54,096 patients were included [26–49], of which 9 were RCTs (n = 1569) and 15 were cohort studies (n = 52,527).…”
Section: Resultsmentioning
confidence: 99%